Tri Tangtu sebagai Suatu Filsafat Hukum Adat - Muhammad Rasyid Ridha S. (Jurnal Hukum Lex Generalis, 2025)
This article examines "Tri Tangtu" as an indigenous philosophy of law that has developed among the Sundanese people in West Java and Banten. Tri Tangtu forms part of the foundational philosophical knowledge and worldview of the Sundanese community in practicing the ancestral traditions of their cultural heritage. Accordingly, this study employs a descriptive-analytical approach, focusing on the philosophical analysis, mythological symbols, customary norms, and the practical implementation of Tri Tangtu. The analysis reveals that Tri Tangtu is not merely a body of knowledge or a set of ethical guidelines but also serves as a foundation for developing customary legal norms, maintaining social order, and resolving issues in daily life.